2005
DOI: 10.1007/s00167-005-0706-x
|View full text |Cite
|
Sign up to set email alerts
|

Avulsion fracture of the posterior cruciate ligament at the tibial insertion in a child: a case report

Abstract: The posterior cruciate ligament (PCL) avulsion fracture from its tibial insertion is a very rare condition in children. An isolated avulsion fracture of PCL in a child and its repair by open reduction and internal fixation with a screw is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
22
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 5 publications
5
22
0
Order By: Relevance
“…Therefore, radiographic analysis is critical for proper diagnosis and treatment. Plain radiographs can be useful to detect an avulsed fragment if it is mostly osseous [20,22,32,34,36]. However, avulsion cannot be ruled out by unremarkable plain films, especially in skeletally immature patients, as was the case in one of our patients [9,22].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Therefore, radiographic analysis is critical for proper diagnosis and treatment. Plain radiographs can be useful to detect an avulsed fragment if it is mostly osseous [20,22,32,34,36]. However, avulsion cannot be ruled out by unremarkable plain films, especially in skeletally immature patients, as was the case in one of our patients [9,22].…”
Section: Discussionmentioning
confidence: 80%
“…Although clinical findings such as a posterior tibial sag and provocative physical examination maneuvers such as the posterior drawer and quadriceps-active test are hallmarks of PCL insufficiency, no physical examination maneuvers can differentiate a substance tear from an avulsion injury [6,7,11,14,20,32,34,36]. Therefore, radiographic analysis is critical for proper diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence to suggest that surgical ORIF should be actively implemented when fracture fragment displacement is more than 1 cm or when conservative treatment has failed. (12,13) The current surgical options for PCL avulsion fractures of the tibia include arthroscopic repair and ORIF. First reported in 1995, arthroscopic treatment of tibial avulsion fractures has since received much attention with the progress of arthroscopic techniques.…”
Section: Discussionmentioning
confidence: 99%
“…1 These injuries have included both "peel-off" and avulsion patterns in the femur, 2,3 midsubstance injuries, 4 and injuries of the tibial attachment. 5 Several authors have suggested that midsubstance injuries are much less common than femoral origin or tibial attachment injuries. 1 Treatment of PCL injuries remains controversial in patients with open physes.…”
mentioning
confidence: 99%